Experimental designs - Cochran, William Gemmell (Wiley, 1992)
The Second Edition of brings this handbook up to date, while retaining the basic framework that made it so popular. Describes the most useful of the designs that have been developed with accompanying plans and an account of the experimental situations for which each design is most suitable